2016
DOI: 10.1182/blood.v128.22.2637.2637
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Response of Platelet Rich Plasma (PRP) for Androgenetic Alopecia Showed No Correlation with Growth Factors and Platelet Number

Abstract: Background: Androgenetic alopecia (AGA) is characterized by a pattern hair loss. Currently, treatment with platelet-rich plasma (PRP) has shown promising results due to the growth factors (GFs) released by the platelets. However, the analysis of therapeutic response according to GFs levels and platelet number in PRP has not been established. Objective: Investigate the therapeutic response to treatment of AGA using a standard method of PRP preparation, and the relation with GFs levels and platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thirteen studies (54%) reported statistically significant improvement in at least one objective outcome. Hair counts or hair densities were described by 16 studies, 15,17,20,21,23,24,26,28,[30][31][32][33][34][35][36][37] and of these, 12 found statistically significant improvements in one of these objective outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies (54%) reported statistically significant improvement in at least one objective outcome. Hair counts or hair densities were described by 16 studies, 15,17,20,21,23,24,26,28,[30][31][32][33][34][35][36][37] and of these, 12 found statistically significant improvements in one of these objective outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…41 Anitua et al used a P-PRP system. 15 Tawfik et al, 34 Farid et al, 33 Jha et al, 16 Kachhawa et al, 17 Rodrigues et al, 20 Singhal et al, 22 and Khatu et al 24 used L-PRP based on descriptions of their preparations that included the buffy coat in their second step hard spin centrifugation. Gentile et al, 30 Borhan et al, 21 Betsi et al, 27 Gkini et al, 23 and Kang et al 37 referenced L-PRP systems (Regen or SmartPrep), but newer kits could variably generate L-PRP or P-PRP.…”
Section: Discussionmentioning
confidence: 99%